ANALYSIS OF LOCAL TAX GOVERNANCE IN INCREASING LOCALLY GENERATED REVENUE AND FISCAL INDEPENDENCE IN JEMBER REGENCY - Annisa Hangesti Prihaningrum; Norma Ellya Roziana; Izza Mutia Aqila; Keisya Reydi Natasya S.; Narizky Nur Fakhri M.; Rafael Benino Ampangallo B.; Revienda Anita Fitrie; Melda Fadiyah Hidayat (Jurnal Administrasi Publik dan Kebijaka (JAPK), 2026)
Local fiscal independence represents the ability of local governments to independently finance development and public services by optimizing Local Own-Source Revenue (Pendapatan Asli Daerah or PAD). This study aims to analyze the level of fiscal independence of Jember Regency in 2025 based on the contribution of local taxes to PAD. The research employs a qualitative approach with a descriptive research design. The data used consists of secondary data obtained from regional budget execution reports (APBD), PAD data, government publications, journals, books, and relevant online media. Data analysis was conducted qualitatively and descriptively using the fiscal independence ratio, which is calculated by dividing PAD by total regional revenue and then multiplying by 100 percent. The result of this ratio calculation is then interpreted into levels of fiscal independence, ranging from very low to high or independent. The results of the study show that Jember Regency has experienced a significant increase in PAD in recent years. Local taxes have become the main component contributing to this increase, primarily through the Street Lighting Tax, Motor Vehicle Tax, and other tax sectors. Based on the analysis of the fiscal independence ratio, Jember Regency falls into the medium or participatory category. This indicates that the local government has developed a reasonably good capacity to finance its regional needs independently, although some dependence on transfer funds from the central government remains. This condition encourages the local government to continuously optimize local tax revenues through the digitalization of tax services, improving taxpayer compliance, as well as strengthening the supervision and management of regional finances. Consequently, the increase in PAD is expected to strengthen the fiscal independence of Jember Regency sustainably in the future.